Neraca Air Dengan Metode Thornthwaite dan Matter di DAS Konto Hulu - Eko Noerhayati (Jurnal Rekayasa Sipil, 2013)
The social activities in watershed area, should be taken in to account in order to keep land conservation.  Land conservation at  watershed of Konto upstream is very important because will influence water source management and it can result flood at watershed of Konto downstream .Water availability prediction upstream watershed will be able to be anticipated with Thornwaite-Matter method.  Water balance at Konto watershed  has deficit 258,4 mm and surplus 711,1 mm. The everage value of dryness index is  7,54Kata kunci: Neraca air, daerah aliran sungai